Chasing a pot of gold: an analysis of emerging recovery-oriented addiction policies in Flanders (Belgium) and The Netherlands. (3rd September 2021) - Bellaert, Lore; Martinelli, Thomas F.; Vanderplasschen, Wouter; Best, David; van de Mheen, Dike; Vander Laenen, Freya
Abstract: Following the paradigm shift to recovery in the Anglophone world, recovery is also gaining momentum in drug policy and practice in Flanders (Belgium) and the Netherlands. Since the meaning of recovery is being debated internationally, broadening the assessment of how the recovery framework is applied in policy discourse and how it is implemented in various international contexts is imperative. This comparative policy analysis aims to assess similarities and differences in addiction recovery vision, implementation, and evaluation in Flanders and the Netherlands. The thematic analysis draws upon a triangulation of different data collection methods: a focus group ( n = 14) and interviews ( n = 21) with key figures in the addictions field, followed by analyses of relevant policy documents ( n = 9). Our findings show that a holistic vision of addiction recovery is endorsed in both countries. Although differences in policy development occurred (i.e. centrally driven in Flanders versus 'bottom-up' in the Netherlands), similar challenges emerged concerning recovery-oriented addiction policies. While policymakers in Flanders and the addiction sector in the Netherlands strongly proclaim recovery, structural implementation, dedicated funding, and systematic evaluation of recovery-oriented policies are lacking. This study suggests that systematic inclusion of experts by experience and aligning government and practice level funding and policies are crucial.